Integrating Blockchain Technology into e-HRM Practices in the New Era of Digital HRM - Suba Durairaj; Arockiam Kulandai; Vinoth Durairaj (APPS Publications, 2025)
The study aims to explore how blockchain technology can be integrated into Human Resource Management (HRM) to improve organizational processes. Specifically, it examines its impact on recruitment, training, data protection, and performance management. The researchers conducted a systematic review of 34 peer-reviewed studies. These sources were gathered from major academic publishers such as Sage, Taylor & Francis, Wiley, and Emerald. The review indicates that blockchain enhances the efficiency and security of HR technology frameworks. It effectively strengthens electronic HRM (e-HRM) practices by providing a more robust and optimal way to manage resource data. This study shifts the focus of blockchain from its traditional association with cryptocurrency to its emerging role as a strategic data management tool for HR. It provides a synthesized look at how blockchain interacts with other advanced technologies like AI and robotics within the specific context of HR innovation.